2015
DOI: 10.3923/ijss.2015.63.73
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Biochar Produced at Different Temperatures and its Effect on Acidic Nitosol of Jimma, Southwest Ethiopia

Abstract: Physical and chemical properties of the biochar varied as a function of feedstock selection and pyrolysis temperatures. Biochar additions to acidic soils have the potential to improve soil fertility and crop yield. Biochar materials were produced from coffee husk and corn cob at temperatures of 350 and 500°C and characterized by their physical and chemical properties. These were mixed with acidic soil at the rates of 0, 5, 10 and 15 t haG 1 and were laboratory incubated for 2 months at ambient temperature to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 26 publications
(34 reference statements)
2
27
1
1
Order By: Relevance
“…Available P and K increased with increasing pyrolysis temperature from 350 °C to 650 °C. Berecha et al (2015) also observed similar results in their experiment using coffee husk and corn cob biochar where available P content and exchangeable cation contents increased when pyrolysis temperatures increased from 350 °C to 500 °C. In general, slow pyrolysis of feedstock produces biochar with higher available P and Mg (Ippolito et al, 2015).…”
Section: Changes In Chemical Propertiessupporting
confidence: 77%
See 1 more Smart Citation
“…Available P and K increased with increasing pyrolysis temperature from 350 °C to 650 °C. Berecha et al (2015) also observed similar results in their experiment using coffee husk and corn cob biochar where available P content and exchangeable cation contents increased when pyrolysis temperatures increased from 350 °C to 500 °C. In general, slow pyrolysis of feedstock produces biochar with higher available P and Mg (Ippolito et al, 2015).…”
Section: Changes In Chemical Propertiessupporting
confidence: 77%
“…Moreover, it was observed that in RHB without ERP, the available magnesium (Mg) content has increased by two-fold when the pyrolysis temperature increases from 350 °C to 650 °C. The higher cation concentrations at higher temperatures are due to hydrolysis of carbonates and bicarbonates of base cation in feedstock material (Berecha et al, 2015). This trend was not observed with ERP added RHB but a substantially higher Mg levels were resulted at 500 °C and 650 °C temperatures (Table 1).The quantity of available nutrients from the total varied with the type of nutrient.…”
Section: Changes In Chemical Propertiesmentioning
confidence: 92%
“…Ash residues contain carbonates and bicarbonates of cations such as Ca 2+ , Mg 2+ , Na 2+ , and K + (Weyers and Spokas 2014;Domingues et al 2017). Variability in pH causes changes in the availability of hydrogen, iron and aluminum ions which affects the interaction and transport of water and nutrients across the plants cell membrane (Bayu et al 2015). For example, under acidic soil conditions, precipitation reactions occur between inorganic phosphorus (HPO 4 2− ) with aluminum (Al) and iron (Fe) forming Al-P and Fe-P minerals rendering P unavailable to plants (Bayu et al 2015).…”
Section: Biochar Phmentioning
confidence: 99%
“…Variability in pH causes changes in the availability of hydrogen, iron and aluminum ions which affects the interaction and transport of water and nutrients across the plants cell membrane (Bayu et al 2015). For example, under acidic soil conditions, precipitation reactions occur between inorganic phosphorus (HPO 4 2− ) with aluminum (Al) and iron (Fe) forming Al-P and Fe-P minerals rendering P unavailable to plants (Bayu et al 2015). Baronti et al (2014) reported that soils with higher pH tend to increase P availability by decreasing Al +3 and H + ions in cation exchange sites.…”
Section: Biochar Phmentioning
confidence: 99%
See 1 more Smart Citation